The Effect of Zircon Filler Percentage, Viscosity, Coating Amount, and Agitation on The Fettling Duration of Track Shoes - Tiwan; G. Yudha Fatria Egiansyah (Journal of Applied Mechanical Engineering Innovation, 2025)
Metal penetration defects can slow down the fettling duration. This study examines the effect of zircon filler percentage, viscosity level, coating amount on the mold, and agitation on fettling duration in the metal casting process of the Komatsu PC2000 Excavator Track Shoe. The research method used was a True Experimental Post-test Only Control Design. The research samples were randomly taken from molds that were in production, and the data analysis technique used was descriptive statistics. Based on the results, changing the coating from 60% zircon to 80% zircon can reduce the fettling duration by about 10 minutes. If the viscosity of the 80% zircon coating is reduced to 55-60 Baume, the fettling duration can be shortened by up to 23 minutes. However, this would increase production costs by Rp. 38,532,900 per month. To address this, the coating mass on the mold was reduced by one-third, shortening the fettling duration by 20 minutes, with an additional cost of only Rp. 3,333,000 per month. Moreover, applying agitation to the 60% zircon coating can reduce fettling duration by up to 29 minutes without any additional costs.